COMPARATIVE ANALYSIS OF ISLAMIC INHERITANCE LAW ON INHERITANCE RIGHTS IN ACEH, REPUBLIC OF INDONESIA AND PATTANI, SOUTH THAILAND - Imam A' Ardhana Lubis; Faisal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the inheritance law systems in Aceh (Indonesia) and Pattani (Thailand), two regions with strong historical, cultural, and Islamic backgrounds. Aceh implements Islamic inheritance law integrated into the national legal system through the Sharia Court, while the Muslim community of Pattani practices Islamic inheritance law in a limited manner within the context of Thailand's secular national law. This study employed qualitative methods with a juridical-normative and sociological approach, through literature review, analysis of legislation, and an examination of social practices. The results show that although both regions adhere to the principles of Islamic inheritance law, there are significant differences in their application and formal legal force. In Aceh, Islamic inheritance law has strong legal legitimacy and is recognized by the state, while in Pattani, its application is more cultural and depends on the agreement of families and religious leaders. This research is expected to contribute to the comparative study of Islamic law and an understanding of the dynamics of the application of Islamic inheritance law in Muslim-majority and minority regions.